1979
DOI: 10.1039/f19797501226
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in paraffin hydrocarbons. Diffusion of cyclohexylbromide in n-alkanes at 25°C

Abstract: The general applicability of the Stokes-Einstein relation for diffusion has been studied for the case of cyclohexylbromide diffusing in n-alkanes with special reference to the size relationship between the solute and solvent molecules.The plot of Do against l/qo (Do = mutual diffusion coefficient at infinite dilution, yo = solvent viscosity) yields two straight lines with their point of intersection at about n-nonane (C9). This appears to conform with a more generalized form of the Stokes-Einstein theory also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Amu reported the diffusion coefficient of cyclohexylbromide in various paraffin hydrocarbons. He found that in these solvents x is not a constant but decreases with increasing chain length of the hydrocarbons; that is, x corresponding to n -heptadecane (C 17 ) is about 1.8 times smaller than that corresponding to n -hexane (C 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Amu reported the diffusion coefficient of cyclohexylbromide in various paraffin hydrocarbons. He found that in these solvents x is not a constant but decreases with increasing chain length of the hydrocarbons; that is, x corresponding to n -heptadecane (C 17 ) is about 1.8 times smaller than that corresponding to n -hexane (C 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…We refer to the studies of Amu for a more detailed discussion. 19 A common feature of the data is the characteristic negative values of the hydrodynamic virial coefficient, k D . The latter is defined by where A 2 is the second virial coefficient, M the molar mass, k f the concentration-dependent friction factor, and V 2 the solute partial specific volume.…”
Section: Resultsmentioning
confidence: 99%
“…We note here that for particles larger than the solvent molecules, the factor 6π in eq 7 is appropriate, whereas for diffusing particles only slightly larger than or approximately equal to the size of the solvent molecules, the factor should be replaced by 4π. We refer to the studies of Amu for a more detailed discussion . A common feature of the data is the characteristic negative values of the hydrodynamic virial coefficient, k D .…”
Section: Resultsmentioning
confidence: 99%
“…where B is the Boltzmann constant (1.3806 ϫ 10 Ϫ23 J K Ϫ1 ), c is a constant ͑4 and 6 for the slip and stick boundary conditions, respectively͒, 38,39 is the solvent viscosity, and r s is the radius of the diffusing molecule modeled as a sphere. The obtained dependence of D O 2 on does not fit that expected from the Stokes-Einstein equation, as readily seen from Fig.…”
Section: Discussionmentioning
confidence: 99%